UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENGATASI PERILAKU SISWA YANG MELANGGAR TATA TERTIB DI SDN 03 PAKAN LABUAH, BUKITTINGGI - Nani Febi Nur Aini; Afrinaldi (CV. ADIBA AISHA AMIRA, 2024)
This article is crafted to present information regarding student behavior that infringes upon school regulations, with the primary objectives of (1) identifying the factors influencing such behavior, (2) exploring the efforts made by guidance and counseling (BK) teachers in addressing these behaviors, and (3) examining the supporting and hindering elements in the process of addressing student misconduct. The research methodology employed involves a direct field approach, utilizing qualitative methods, and employing observation and interview as data collection instruments. The supportive factors identified among BK teachers in addressing the behavior of students at SDN 03 PAKAN LABUAH, BUKITTINGGI, include effective collaboration among teachers, the implementation of habituation programs within the school, and cooperative efforts with parents. On the other hand, inhibiting factors encompass challenges both external and internal to the school environment, along with a lack of awareness among the students themselves.